Desalination for Syria - Wardeh S.; Morvan H.P.; Wright N.G. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
Several countries, such as Saudi Arabia, The United Arab Emirates and Qatar have indeed implemented vast desalination programmes with success. This paper is interested in the potential of such technology for Syria, a country which has yet to implement such an initiative. A feasibility study is presented that compares the geographical, demographic and water resources conditions, as well as the country's infrastructure and economics in countries where desalination has been implemented, in order to identify key features and compare them with the Syrian context. A technical review of water desalination methods is subsequently presented. Key features and problems relevant to Syria are highlighted. Furthermore the suggestions made by the Desalination Commission in Syria are analysed. Finally, an attempt is made to identify potential scientific and technical progress that could be beneficial to the Syrian model and ambition.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)